Study of Single Subcutaneous Injection for Digital Block Using Lignocaine with Adrenaline - Pudasaini, Pushkar; Rai, Shankar Man; Nakarmi, Kiran; Chaurasia, Lok Raj (Journal of Nepalgunj Medical College, 2022)
It is known fact that adding adrenaline to local anesthetic gives many advantages but it is not practiced commonly in digital anaesthesia due to fear of ischemia due to resultant vasoconstriction. Total five cases were there. All patients received lignocaine with adrenaline in digital block. Recent literature and our findings both suggest use of adrenaline in at least a well perfused finger is safe and may give some potential advantages.